Deletion of PTEN produces autism-like behavioral deficits and alterations in synaptic proteins - Lugo, Joaquin N.; Smith, Gregory D.; Arbuckle, Erin P.; White, Jessika; Holley, Andrew J.; Floruta, Crina M.; Ahmed, Nowrin; Gomez, Maribel C.; Okonkwo, Obi (Frontiers in Molecular Neuroscience, 2014)
Many genes have been implicated in the underlying cause of autism but each gene accounts for only a small fraction of those diagnosed with autism. There is increasing evidence that activity-dependent changes in neuronal signaling could act as a convergent mechanism for many of the changes in synaptic proteins. One candidate signaling pathway that may have a critical role in autism is the PI3K/AKT/mTOR pathway. A major regulator of this pathway is the negative repressor phosphatase and tensin homolog (PTEN). In the current study we examined the behavioral and molecular consequences in mice with neuron subset-specific deletion of PTEN. The knockout (KO) mice showed deficits in social chamber and social partition test. KO mice demonstrated alterations in repetitive behavior, as measured in the marble burying test and hole-board test. They showed no changes in ultrasonic vocalizations emitted on postnatal day 10 or 12 compared to wildtype (WT) mice. They exhibited less anxiety in the elevated-plus maze test and were more active in the open field test compared to WT mice. In addition to the behavioral alterations, KO mice had elevation of phosphorylated AKT, phosphorylated S6, and an increase in S6K. KO mice had a decrease in mGluR but an increase in total and phosphorylated fragile x mental retardation protein. The disruptions in intracellular signaling may be why the KO mice had a decrease in the dendritic potassium channel Kv4.2 and a decrease in the synaptic scaffolding proteins PSD-95 and SAP102. These findings demonstrate that deletion of PTEN results in long-term alterations in social behavior, repetitive behavior, activity, and anxiety. In addition, deletion of PTEN significantly alters mGluR signaling and many synaptic proteins in the hippocampus. Our data demonstrates that deletion of PTEN can result in many of the behavioral features of autism and may provide insights into the regulation of intracellular signaling on synaptic proteins.